Pengaruh Relaksasi Otot Progresif Untuk Menurunkan Nyeri Pada Penderita Nefrolithiasis Di Rumah Sakit Tk III Dr.R Soeharsono Banjarmasin - Ariani, Sri Purwanti; Sri Jamilah; Yuhansyah; Sarifa (CV. ITTC INDONESIA, 2024)
Complaints of nephrolithiasis in each patient depend on the position or location of the stone, size of the stone, and resulting complications. Common complaints include flank pain, back pain, hematuria (blood in the urine), stone obstruction leading to urinary flow blockage and urinary tract contamination, fever, chills, and feelings of anxiety. However, pain is a common and frequently experienced symptom in every nephrolithiasis patient. Pain is an unpleasant sensory and emotional sensation associated with tissue damage or other factors, causing individuals to feel distressed and suffer, thereby disrupting daily activities, psychological well-being, and more. Acute pain is a sensory or emotional experience related to actual or potential tissue damage, with a sudden or gradual onset and an intensity ranging from mild to severe, lasting less than 3 months. Various non-pharmacological methods, including progressive muscle relaxation techniques, can help reduce pain.